The Influence Of Village Government Competency, Transparency, Public Participation And Utilization Information Technology Towards Accountability Village Fund Management (Case Study In Villages In Nawangan District, Pacitan Regency) - Lestari, Rina Puji; Wijianto , Wijianto; Hartono , Sri (Nomico, 2025)
Accountability in the management of village funds is a demand for the village government as the manager of village funds as a form of implementation of Law No. 6 of 2014 concerning Villages. Influence factors that arise related to village fund management accountability are Village Government Competence, Transparency, Community Participation and Utilization of Information Technology. This study aims to examine the effect of Village Government Competence, Transparency, Community Participation and Utilization of Information Technology on the accountability of village fund management in the Nawangan District, Pacitan Regency. This type of research is quantitative research. The data was collected using a questionnaire with 108 respondents consisting of village officials and the Village Consultative Body (BPD) in 9 villages in the Nawangan District, Pacitan Regency. The data analysis method used was multiple linear analysis using the SPSS version 25 program. The results showed that village government competence, transparency and the use of information technology had a positive effect on village fund management accountability. The results of further research indicate that community participation does not affect the accountability of village fund management